Rosette-Forming Glioneuronal Tumor at Septum Pellucidum: Insights Gained from a Common Tumor at Rare Location - Maruti Nandan; Ashish Patnaik; Rabi Narayan Sahu; Yashveer Singh; Ved P. Maurya; Kuntal K. Das; Sanjay Behari (Indian Journal of Neurosurgery)
The rosette-forming glioneuronal tumor (RGNT) is an uncommon entity and carries a special character because of its mixed glial and neuronal composition in the histomorphological appearance. These lesions have a benign character and carry a good outcome if undergoes gross total resection. Over the past 15 years, there have been a significant change in their nomenclature depending upon the location to histological composition. Herein, we report an interesting case of a 26-year-old lady who was diagnosed to have the lesion at the septum pellucidum with significant symptoms in the form of headache and seizure episodes. A gross total resection was achieved and she made an uneventful recovery. We discuss the literature on the incidence, location, and histological characteristics of the RGNT in various age groups.